Methodological considerations for the assessment of ADP induced platelet aggregation using the Multiplate® analyser. (June 2013) - Johnston, Lisa R.; Larsen, Peter D.; La Flamme, Anne C.; Harding, Scott A.
<x xml:space="preserve">Abstract</x> Factors affecting the Multiplate® assay's analytical precision have not been well defined. We investigated the effect of methodological factors on the measurement of ADP-induced platelet aggregation using the Multiplate® assay. ADP-induced platelet aggregation was analysed in whole blood using the Multiplate® assay. We tested the reproducibility of measurement, the effect of different anticoagulants (hirudin, citrate and heparin) and the effect of time delay (15, 30, 45, 60, 120 and 180 minutes) between sampling and analysis in patients. The use of a manual calibrated pipette with the Multiplate® analyser was also tested. The mean coefficient of variation (CV) using the manufacturers recommended methods was 10.8 ± 8.7% (n = 30). When compared to hirudin (359.5 ± 309 AU*min) the use of heparin (521.0 ± 316 AU*min, p = 0.0015) increased platelet aggregation, while the use of sodium citrate (245.0 ± 209 AU*min, p = 0.003) decreased the platelet aggregation (n = 20). The addition of CaCl2 to the citrate-anticoagulated blood resulted in platelet aggregation levels similar to hirudin. Platelet aggregation varied with time delay (n = 20). When compared to platelet aggregation at 30 minutes (391.1 ± 283 AU*min), platelet aggregation was reduced at 60 minutes (335.2 ± 251.6 AU*min, p < 0.05), 120 minutes (198.8 ± 122.9 AU*min, p < 0.001) and 180 minutes (160.7 ± 92 AU*min, p < 0.001). The use of a manual calibrated pipette did not significantly reduce the mean CV in the assay (n = 20). Methodological factors such as the anticoagulant used and the time delay should be standardised where possible to reduce variability, and allow thresholds derived from one study to be comparable across multiple studies.